Metabolic reprogramming and immunosenescence in colorectal cancer: mechanisms and therapeutic implications - Zhu, Jun; Shen, Kuan; Su, Qiang; Yao, Guozhong; Chen, Xiaochen (Frontiers in Cell and Developmental Biology, 2025)
Colorectal cancer (CRC), as a highly prevalent malignant tumor worldwide, has a persistently high incidence and mortality rate. In recent years, metabolic reprogramming and immunosenescence have received extensive attention as key mechanisms for tumorigenesis, development and treatment resistance. Metabolic reprogramming not only provides energy and biosynthetic precursors for tumor cells, but also regulates immune responses by reconstructing the tumor microenvironment (TME). Immunosenescence is characterized by the depletion of effector immune cell function and the increase in the proportion of immunosuppressive cells. The two jointly promote the immune escape and therapeutic resistance of CRC. This article systematically reviews the research progress of metabolic reprogramming and immunosenescence in colorectal cancer and explores the related targeted therapeutic strategies, aiming to provide a new theoretical perspective for the precise treatment of CRC.